A study on the perferences for leadership and management, person-job fit and job satisfaction. - Chieng, Wan Lin. (2013)
Kotter [1990] in his seminal article on “What leaders really do” proposed that leadership and management have different functions and are distinguishable from one another. Lek, Chioang and Ang’s [2012] research found that preferences for leadership and management are distinct but related constructs in a tertiary student population. This report aims to explore the validity of the findings to the working population. Also, it aims to determine whether job functions match individual employees’ personal preferences for leadership or management, leading to purported job satisfaction. Using Lek et al.’s [2012] instrument on leadership and management preferences (LMP), we integrated instruments measuring person-job (PJ) fit and job satisfaction. Job functions were matched with one’s LMP to validate perceived PJ fit. The study was conducted on a population of working adults from 21 years old and above, and included managerial and non-managerial positions. A web-based survey was launched to invite working adults to participate. Results from 93 participants from the survey further confirmed what was tested in the student population – leadership and management were distinct but related, personality has been shown to be more positively related to leadership preference as compared to management preference, while values are more related to the management preference. However, the match between LMP and job functions did not predict PJ fit. Nevertheless, PJ fit was positively related to job satisfaction, showing potential of finding an instrument matching PJ fit and LMP in the future. Limitations and implications for future studies are also discussed, such as tying up with big corporations and incorporating multiple raters to increase results’ validity.